Proyecto de factibilidad para la implementación de una operadora de turismo para la ciudad de Loja, provincia de Loja - Viñán Chamba, María Jaqueline (2015)
This project will run a 'PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A TOUR OPERATOR FOR THE CITY OF LOJA, Loja Province ", and develop tourism service for the benefit of people who want to travel for business or pleasure all parts of the world. And the aim of this study raise a company to provide quality services and value that can contribute to the social, political and economic development of the city of Loja. The summary shall itemize the main steps of the project in creating a tourism operator that contribute to strengthening the economic fabric of this sector, first because there will be opening jobs, which will allow the employee to cover your basket ; and second because it provides an opportunity for investors to execute this project which will generate profitability. In the introduction, a brief analysis of the economic situation of our country and our province in story refers to the implementation of this new company is presented. The methodology presents the techniques of data collection and research methods that were used to present the results of this work. The market started with the implementation of surveys divided by 399 families, achieving determine if there is demand for this product; a story in the offer, just as he polled 84 dealers staples and shops selling this product, allowing to set the parameters required for the analysis. Market Research Company determines that it is feasible to implement it according to the data obtained from the unmet demand of 1,060 services to offer. On the technical study, the size is what I consider the determining factors for adequate infrastructure such as demand, availability of inputs, given this background, the installed capacity is equal to the capacity utilization for the first year of 2,369 tour packages accounting for 94%, and for the following years a percentage increase according to the needs of the Tour Operator, the financial capacity of the company and a physical space that allows for the processes of production and marketing of the finished product. As for project engineering the production process occurs with all phases. According to the study of the organization, has proposed a limited company, the favorable conditions of this type of company. The company will have the company name TOUR OPERATOR "CRISTAL CIA. LTDA", Represented by hierarchical organizational levels for you to govern the organic life of the company. The financial study presents more than the budgets required to establish investment and financing may be $ 57,244.57, project evaluation with every financial indicators such as NPV is 243,794.23, the period capital recovery 1 year, 8 months and 16 days, the cost benefit ratio of 1, 90, where every dollar is 90 cents of profit generated, the IRR is the 81.24% and a sensitivity analysis increased costs of 58.70% and a decrease in income of 27.81%, which determine whether it is advisable to carry out the investment and implementation of the next project